Jejak Toleransi Di Akar Rumput - Triana Rosalina Noor; Wahyu Hidayah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study aims to reveal the forms of tolerance education within Muslim families living in the multi-religious community of Sidodadi Village, Gedangan District, Malang Regency. The research employed a qualitative approach with a case study method, involving ten informants from Muslim families selected purposively. Data were collected through in-depth interviews, observation, and documentation, and then analyzed using data condensation, data display, and conclusion drawing techniques. The findings indicate that tolerance education is carried out through four strategies. First, provisioning, which involves instilling religious and social values that emphasize respect for diversity. Second, habituation, implemented through the practice of living side by side harmoniously with people of different faiths. Third, exemplary, in the form of modeling open attitudes, mutual respect, and appreciation of diversity. Fourth, controlling, which ensures consistency in applying tolerance values in daily interactions. These findings highlight the crucial role of families as the foundation of tolerance education in multi-religious communities, thereby fostering the creation of harmonious social life at the grassroots level.